DIVERSITY OF MICROCHIROPTERAN BATS IN FOREST FRAGMENTS AND RIPARIAN ZONES IN AN OIL PALM PLANTATION ESTATE - Syamsi, Fauziah (Universitas Riau Kepulauan, 2015)
Oil palm is one of the world’s most rapidly increasing crops, and covers over 13 million ha in Southeast Asia. Sumatra has a relatively long history of commercial oil palm cultivation, and many plantations have replaced rain forest. Typically these monoculture plantations support much fewer species than do forest, however there is very little information available for bats. We sampled insectivorous bats in West Sumatra in a mature oil palm plantation where some forest cover was retained in forest fragments on hills and along rivers. Using a total of 180 harp trap nights we compared the bat community in three habitat types: forest patches, riparian zone and plantation area. In total we captured 1108 bats representing 21 species and 5 families, and the majority of these (in terms of species and abundance) were found in forest fragments. Oil palm plantation was found to be a poor habitat for bats – only four individuals of two species were captured. Riparian areas supported intermediate diversity, and might be important as wildlife corridors between forest fragments.